EFFICIENCY OF THE USE OF HEAT PUMPS ON THE CHP PLANTS - Juravleov A.A.; Sit M.L.; Zubaty A.L.; Poponova O.B.; Sit B.M.; Timchenko D.V. (Problems of the Regional Energetics, 2007)
The work is dedicated to the calculus of the efficiency of the use of heat pumps on the CHP plants. There are presented the interdependences between the pay-back period and NPV of heat pump and the price of 1 kWt of thermal power of heat pump and of the tariff of electricity.